Knowledge, attitudes and beliefs about electroconvulsive therapy amongPolish students - Gędek, Adam; Materna, Michał; Święcicki, Łukasz (Current Problems of Psychiatry, 2021)
Introduction. Electroconvulsive therapy (ECT) is an effective and safe treatment for many mental disorders. Nevertheless, the attitudes towards ECT are negative and the use of this method in Poland is decreasing. Aim. The aim of the study was to investigate the general knowledge and attitudes towards electroconvulsive therapy among Polish university students, including students of medicine, psychology and other faculties. Material and methods. An original online questionnaire containing 39 questions was used, distributed through student groups on social networking sites. A total of 418 questionnaires were completed. The collected data were statistically analyzed. Results. Significant knowledge gaps and negative beliefs about electroconvulsive therapy were observed among Polish students. Medical and psychology students had more extensive knowledge and more positive beliefs about this method of treatment than students of other faculties. Greater knowledge of the therapy was associated with a more positive attitude towards it. The main source of knowledge about ECT for students of medicine and psychology were lectures and courses, and for students of other faculties – movies. Students, who considered psychiatry as their future specialization, had less knowledge and a more negative attitude towards ECT, relative to the rest of the respondents. Conclusions. There is a need for educational interventions that will change the way how ECT is perceived both in the public opinion and in the medical community. An effective solution to low levels of knowledge for medical students may be the observation of the procedure included in the study programme.